2020
DOI: 10.32615/ps.2020.027
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response and transcriptomic profiling provide insights into the alkali tolerance of clone halophyte Leymus chinensis

Abstract: Alkali stress is one of the important factors in restricting agriculture production. Leymus chinensis is constructive halophyte species in alkalized grassland in China. In order to investigate the gene expression response of L. chinensis to alkali stress, we used PacBio technology to obtain reference full-length transcript sequences for transcriptomic analysis of alkali stress response. In order to elucidate the alkali tolerance mechanisms of L. chinensis, we measured the photosynthetic parameters, concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Massive accumulation of surplus electrons in the electron transport chain due to a decrease of electron transfer rates causes electron leakage and then accelerates the degree of breakage of PSII reaction center under salt stress ( Zhang et al, 2017 ; Hou et al, 2018 ). In addition, Wang et al (2020) have clarified that compared with salt stress, alkali stress decreased the photosynthetic electron transport rate and stomatal conductance, and also reduced the aerenchyma amount, and then influenced the CO 2 influx into mesophyll cells of Leymus chinensis . Drought stress directly makes the stomata closed, resulting in a reduction of CO 2 absorption and transportation of non-structural carbon (NSC), which is an essential element of the photosynthetic system ( Steppe et al, 2015 ; Hajiboland et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…Massive accumulation of surplus electrons in the electron transport chain due to a decrease of electron transfer rates causes electron leakage and then accelerates the degree of breakage of PSII reaction center under salt stress ( Zhang et al, 2017 ; Hou et al, 2018 ). In addition, Wang et al (2020) have clarified that compared with salt stress, alkali stress decreased the photosynthetic electron transport rate and stomatal conductance, and also reduced the aerenchyma amount, and then influenced the CO 2 influx into mesophyll cells of Leymus chinensis . Drought stress directly makes the stomata closed, resulting in a reduction of CO 2 absorption and transportation of non-structural carbon (NSC), which is an essential element of the photosynthetic system ( Steppe et al, 2015 ; Hajiboland et al, 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…The application of organic acids immediately lowers the soil pH ( Rukshana et al., 2014 ), and plants, such as grape hybrid rootstocks, seabuckthorn, Chloris virgata , wheat and grapevine, can mitigate the damage caused by alkali stress through the secretion of organic acids ( Chen et al., 2009 ; Yang et al., 2010 ; Guo et al., 2018 ; Xiang et al., 2019 ; Li et al., 2020 ). Our previous study revealed that alkali stress strongly inhibits photosynthesis and growth of L. chinensis , and it disturbed the ion balance ( Wang et al., 2020 ). Here, our results indicated that L. chinensis extensively secreted organic acids, phenolic acids, free fatty acids and other substances containing a -COOH or phosphate group after expose to alkali stress.…”
Section: Discussionmentioning
confidence: 99%
“…Plants can respond to salt and alkali stress by accumulating small-molecule osmotic solutes in order to reduce stress damage [6]. Previous research has revealed that when plants are subjected to salt and alkali stress, the concentrations of soluble sugars [14,15,21], organic acids [12,13,15,23,24], amino acids [6,25], and betaine [21] increase, which are the main solutes to resist stress. However, the solutes accumulated by plants in response to salt and alkali stress change depending on different plant species and stress concentrations.…”
Section: Changes In Organic Solutes Under Salt and Alkali Stressmentioning
confidence: 99%
“…As a result, it is one of the most suitable grass species for salinealkali land improvement [1,12]. Currently, researchers are investigating the response of L. chinensis to salt and alkali stress using transcriptome and proteome approaches [13,14], while the physiological response of L. chinensis to salt and alkali stress is currently being investigated only through multiple physiological experiments to study the accumulation of specific metabolites under salt and alkali stress. L. chinensis enhances salt tolerance predominantly by accumulating proline, betaine, and soluble sugar, and alkali tolerance primarily by accumulating organic acids (citric acid, malic acid, succinic acid, acetic acid, and oxalic acid) [12,15].…”
Section: Introductionmentioning
confidence: 99%